PENGARUH CELEBRITY ENDORSER, CITRA MEREK DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK SCARLETT WHITENING (Studi Kasus Pengguna Scarlett Whitening) - Dagma Syafira Destia Wardani; Ali Maskur (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The number of beauty products makes the competition in the beauty world increasingly tight. However, this also results in various factors that consumers consider when buying beauty products. In this study, the factors that influence purchasing decisions are analyzed through celebrity endorsers, brand image, and trust. The purpose of this study was to determine the effect of celebrity endorser, brand image, and trust on purchasing decisions of Scarlett Whitening products. The population in this study were users of the Scarlett Whitening product. The number of samples used was 100 respondents. Sampling using purposive sampling technique. Data were collected by distributing questionnaires. The data analysis method used is multiple linear regression analysis using the SPSS application. Based on statistical tests in this study, the following results obtained: celebrity endorser has a significant positive effect on purchasing decisions, brand image has no effect on purchasing decisions, and trust has a significant positive effect on purchasing decisions